Pathogenicity and virulence of Staphylococcus aureus - Cheung, Gordon Y. C.; Bae, Justin S.; Otto, Michael (Virulence, 2021)
Staphylococcus aureus is one of the most frequent worldwide causes of morbidity and mortality due to an infectious agent. This pathogen can cause a wide variety of diseases, ranging from moderately severe skin infections to fatal pneumonia and sepsis. Treatment of S. aureus infections is complicated by antibiotic resistance and a working vaccine is not available. There has been ongoing and increasing interest in the extraordinarily high number of toxins and other virulence determinants that S. aureus produces and how they impact disease. In this review, we will give an overview of how S. aureus initiates and maintains infection and discuss the main determinants involved. A more in-depth understanding of the function and contribution of S. aureus virulence determinants to S. aureus infection will enable us to develop anti-virulence strategies to counteract the lack of an anti-S. aureus vaccine and the ever-increasing shortage of working antibiotics against this important pathogen.